Portal hypertension. Distal splenorenal anastomosis. Warren operation - Delgado, Bolívar; Praderi, Raúl; Nin Sacarelo, Raúl; Zagia, Miguel; Gómez Fossati, Carlos (Cirugía del Uruguay, 2021)
In this paper the physiopathological fundaments of Warren's operation ( deconnection with distal splenorenal anastomosis) in the treatment of varices of the esophagus and portal hypertension due to cirrhosis, are analyzed. Mention is made of a case operated by us with excellent immediate results. The results obtained by Warren so far, are summarized. It is necessary to achieve greater experience in this type of surgery which we believe to be very valuable when indications are precise.